The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1440-1746.1986.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of chronic Budd‐Chiari syndrome and surgical relief for ‘coarctation’ of the inferior vena cava

Abstract: This report presents the clinical features of 78 cases of the chronic Budd-Chiari syndrome encountered over a period of 13 years. The diagnosis of hepatic venous outflow obstruction was confirmed by venographic studies in all cases. In 20 patients there was hepatic vein occlusion without inferior vena caval (IVC) obstruction (Group A). In 17 patients there was constriction of the IVC above the drainage site of the right hepatic vein which was patent (Group B). In 13 patients there was short segmental obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In the Western world, most patients with BCS have primary hepatic vein thrombosis without MOVC and have an underlying disease that leads to BCS, such as coagulopathy, autoimmune diseases and myeloproliferative diseases 19–21 . In contrast, most patients with BCS in Japan, 2,3,5–7 Nepal, 22 India 23,24 and South Africa 8,9 have MOVC, but the etiology is still unknown. Okuda et al concluded that primary hepatic vein thrombosis (the classical BCS) and IVC obstruction (MOVC) should be considered separately because these two types of BCS are very different in epidemiology, clinical features and natural history 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Western world, most patients with BCS have primary hepatic vein thrombosis without MOVC and have an underlying disease that leads to BCS, such as coagulopathy, autoimmune diseases and myeloproliferative diseases 19–21 . In contrast, most patients with BCS in Japan, 2,3,5–7 Nepal, 22 India 23,24 and South Africa 8,9 have MOVC, but the etiology is still unknown. Okuda et al concluded that primary hepatic vein thrombosis (the classical BCS) and IVC obstruction (MOVC) should be considered separately because these two types of BCS are very different in epidemiology, clinical features and natural history 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In our series, IVC involvement in the majority of cases was due to IVC thrombosis. Previously, MOVC and IVC thrombosis were considered to be idiopathic in origin by most Indian and Asian workers [5,6,11,[13][14][15]17,35,49,50,53,54] ; but this view has been challenged recently in a few reports [22,29,30,42,[55][56][57][58] . In cases of IVC thrombosis in our study, the etiology was identified in 50%.…”
Section: Discussionmentioning
confidence: 99%
“…All previous Indian series, except two [29,32] , describe the predominance of IVC up to 79.2% [7,9,[11][12][13]15,30,39,40,42] or IVC-HV obstruction up to 57.7% [14,24,25,35] ; HV involvement was described in 0%-32% of cases in these series [7,9,[11][12][13][14][15]24,25,30,35,39,40,42] . Of the two distinct previous series, one (total 53 cases) showed similar frequency of HV (35.8%), IVC (33.9%) and combined IVC-HV involvement (30.1%) [29] ; whereas the other series involving only chronic BCS showed predominance of HV (45.9%) followed by combined IVC-HV (29.7%) and IVC involvement (24.3%) [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients are adults, and this simple fact alone speaks against the congenital theory; clinical presentations of child cases are the same as adults 20,21 . Victor et al 8 and Madanagopalan et al 22 who long maintained that IVC stenosis confined to the hepatic portion is an equivalent of coarctation of the aorta, have recently changed their stance and admit that IVC stenosis could be sequela to thrombosis; they experienced filariasis along IVC that caused thrombosis and subsequent stenosis 23 . Kage et al studied 16 autopsy cases of Budd–Chiari syndrome in Japan, the majority being MOVC, and demonstrated that the membrane was an organized old thrombus often consisting of several portions of varying ages 24 .…”
Section: Classification Of Hepatic Vein Outflow Block Modified From Rmentioning
confidence: 99%